Persons: Understanding Psychological Selfhood and Agency - Martin, Jack.; Sugarman, Jeff H.; Hickinbottom, Sarah; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Persons Understanding Psychological Selfhood and Agency Jack Martin, Jeff Sugarman, and Sarah Hickinbottom At its core, psychology is about persons: their thinking, their problems, the improvement of their lives. The understanding of persons is crucial to the discipline. But according to this provocative new book, between current essentialist theories that rely on biological models, and constructionist approaches based on sociocultural experience, the concept of the person has all but vanished from psychology. Persons: Understanding Psychological Selfhood and Agency recasts theories of mind, behavior, and self, synthesizing a range of psychologists and philosophers to restore the centrality of personhood$1 (Bespecially the ability to make choices and decisions$1 (Bto the discipline. The authors$1 (Bunique perspective de-emphasizes method and formula in favor of moral agency and life experience, reveals frequently overlooked contributions of psychology to the study of individuals and groups, and traces traditions of selfhood and personhood theory, including: The pre-psychological history of personhood. A developmental theory of situated, agentive personhood. The political disposition of self as a kind of understanding. Human agency as a condition of personhood. Emergentist theories in psychology. The development of the perspectival self. Persons represents an intriguing new path in the study of the human condition in our globalizing world. Researchers in developmental, social, and clinical psychology as well as social science philosophers will find in these pages profound implications not only for psychology but also for education, politics, and ethics.s
A Theory of Persons and Selves for Psychology -- Introduction: The Problem of Selves and Persons in Psychology -- A Theory of Self and Personhood for Psychology -- The Political Disposition of Self as a Kind of Understanding -- Human Agency and the Irreducibility of Persons -- Persons and Moral Agency -- Emergent Persons -- John Macmurray$1 (Bs Philosophy of the Personal and the Irreducibility of Persons -- Perspectives, Selves, and Persons -- Real Perspectival Selves -- Perspectival Selves in Interaction with Others: Re-reading G.H. Mead$1 (Bs Social Psychology -- Perspectives and Persons: Ontological, Constitutive Possibilities -- The Psychology of Persons: An Idea Whose Time Has Come (Again).s
Keywords: Psychology; Philosophy and social sciences; Clinical psychology; Developmental psychology; Personality; Social psychology; Psychology; Clinical Psychology; Developmental Psychology; Personality and Social Psychology; Philosophy of the Social Sciences; Electronic books